Adherence and/or discontinuation of imatinib mesylate in patients with chronic myeloid leukemia (Brazilian Journal of Pharmaceutical Sciences, 2016)
Adherence to imatinib mesylate improves clinical outcomes and promotes a reduction in health expenditure. However, treatment duration and lack of efficacy decrease adherence to pharmacotherapy, resulting in increased mortality associated with Chronic Myeloid Leukemia. This study aimed to evaluate and compare adherence and/or discontinuation of imatinib mesylate in different studies from the literature. An integrative review of original articles published between the years of 2004 and 2014 was performed using the databases PubMed/MEDLINE, Scopus and SciELO. The descriptor "imatinib" was used in two combinations employing the connector AND between terms: "medication adherence'' AND ''imatinib" AND "leukemia'' and ''patient compliance'' AND "imatinib" AND "leukemia". We identified 476 studies, being 14 included in the study. The rates of adherence and discontinuation were diverse, ranging from 19.0 to 97.0% and from 1.8 and 41.0%, respectively, and a high number of longitudinal studies was observed (71.4%). Most studies used questionnaires as an indirect method to assess adherence and factors related to poor adherence were adverse drug reactions, dose changes and unavailability of the medication. Patient education associated with follow up by pharmacists and other health professionals can improve patient adherence and minimize the pharmacotherapy discontinuation.